Talking comics with Minimum Wage creator Bob Fingerman. Issue 2 (2nd April 2016) - Klaehn, Jeffery
Abstract : Artist and writer Bob Fingerman is the creator of the comic book series Minimum Wage and the critically acclaimed graphic novels White Like She, Beg the Question and From the Ashes . He is also the author of two prose novels, Bottomfeeder (2006) and Pariah (2010). In this interview he discusses the evolution and publication history of Minimum Wage within the context of his work and career to date. Additional topics explored within the interview include his art and writing process; how European comics have historically differed from North American comics in terms of approach and aesthetic principles; comic strip art; the art and influence of Heavy Metal magazine, Moebius (Jean Giraud), Richard Corben, and Gahan Wilson; and prioritising creator-owned work over work-for-hire.